2015
DOI: 10.11138/mltj/2015.5.3.156
|View full text |Cite
|
Sign up to set email alerts
|

Can Platelet rich plasma stimulate human ACL growth in culture? A preliminary experience

Abstract: Can Platelet rich plasma stimulate human ACL growth in culture? A preliminary experience ter than 5% PRP. 5% PPP had no significant effect on cell viability, but it led to an increase in DNA content in 5 of 11. There was no statistically significant effect of either PRP or PPP in preventing cell death (depicted by apoptosis rate). Conclusion: PRP may have an enhancing effect on ACL cell viability and promotion of cell proliferation but the ideal concentration of PRP for these positive effects needs to be deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Over the past several years, there has been increasing interest in biologic agents as both nonoperative treatment modalities and augments to surgical procedures, to potentially accelerate the healing process and expedite return to sport after muscle injury. Platelet-rich plasma (PRP) is a blood product that is rich in platelets and many different cytokines and growth factors, such as transforming growth factor beta (TGF-β1), insulin-like growth factor-1 (IGF-1), and vascular endothelial growth factor (VEGF), whose influence on the healing of ligaments, muscles, tendons, joints, and soft tissue has been extensively studied[1-5]. In muscle pathology in particular, PRP’s abundance of growth factors and cytokines is purported to expedite healing through the induction of cellular proliferation and migration, increased angiogenesis, and muscle tissue regeneration[6-8].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, there has been increasing interest in biologic agents as both nonoperative treatment modalities and augments to surgical procedures, to potentially accelerate the healing process and expedite return to sport after muscle injury. Platelet-rich plasma (PRP) is a blood product that is rich in platelets and many different cytokines and growth factors, such as transforming growth factor beta (TGF-β1), insulin-like growth factor-1 (IGF-1), and vascular endothelial growth factor (VEGF), whose influence on the healing of ligaments, muscles, tendons, joints, and soft tissue has been extensively studied[1-5]. In muscle pathology in particular, PRP’s abundance of growth factors and cytokines is purported to expedite healing through the induction of cellular proliferation and migration, increased angiogenesis, and muscle tissue regeneration[6-8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the improvement was much better in the PRP group than in the corticosteroid group with better foot scores and lower pain scores. Stimulation of human ACL growth in culture by PRP in an in vitro study 14 : Analysis of cultured cells showed that addition of PRP (5 or 10%) increased the viability of ACL cells in 4 out of 11 and promoted cell proliferation in 8 of 11 donor samples; 10% PRP was more effective than 5% PRP. However, the difference in effectiveness of 10% PRP was not significantly better than 5% PRP; 5% PPP had no significant effect on cell viability, but it led to an increase in the DNA content in 5 of 11.…”
Section: Resultsmentioning
confidence: 99%
“…3. Stimulation of human ACL growth in culture by PRP in an in vitro study 14 : A controlled laboratory study was designed and ACL remnants were collected from the tibial stump of torn ACL with a punch from 28 patients during arthroscopic ACL reconstruction. Successful primary culture was obtained in 11 out of 28 samples of ACL remnant tissue; cells were isolated, identified, and cultured and were then divided into six groups: a.…”
Section: Methodology Of Six Studies Done At Pgimermentioning
confidence: 99%
“…Dhillon et al [28] evaluated the effect of human ACL cell growth of 11 patients during ACL reconstruction surgery. The ACL remnants were collected, and the cells were isolated, identified and cultured and then divided into six groups.…”
Section: Use Of Platelet-rich Plasma In Muscle and Ligament Injuriesmentioning
confidence: 99%